IWGDF guidance on the prevention of foot ulcers in at‐risk patients with diabetes. (26th January 2016) - Bus, S. A.; van Netten, J. J.; Lavery, L. A.; Monteiro‐Soares, M.; Rasmussen, A.; Jubiz, Y.; Price, P. E.
Recommendations: To identify a person with diabetes at risk for foot ulceration, examine the feet annually to seek evidence for signs or symptoms of peripheral neuropathy and peripheral artery disease. (GRADE strength of recommendation: strong; Quality of evidence: low) In a person with diabetes who has peripheral neuropathy, screen for a history of foot ulceration or lower‐extremity amputation, peripheral artery disease, foot deformity, pre‐ulcerative signs on the foot, poor foot hygiene and ill‐fitting or inadequate footwear. (Strong; Low) Treat any pre‐ulcerative sign on the foot of a patient with diabetes. This includes removing callus, protecting blisters and draining when necessary, treating ingrown or thickened toe nails, treating haemorrhage when necessary and prescribing antifungal treatment for fungal infections. (Strong; Low) To protect their feet, instruct an at‐risk patient with diabetes not to walk barefoot, in socks only, or in thin‐soled standard slippers, whether at home or when outside. (Strong; Low) Instruct an at‐risk patient with diabetes to daily inspect their feet and the inside of their shoes, daily wash their feet (with careful drying particularly between the toes), avoid using chemical agents or plasters to remove callus or corns, use emollients to lubricate dry skin and cut toe nails straight across. (Weak; Low) Instruct an at‐risk patient with diabetes to wear properly fitting footwear to prevent a first foot ulcer, either plantar or non‐plantar, or a recurrent non‐plantar foot ulcer. When a foot deformity or a pre‐ulcerative sign is present, consider prescribing therapeutic shoes, custom‐made insoles or toe orthosis. (Strong; Low) To prevent a recurrent plantar foot ulcer in an at‐risk patient with diabetes, prescribe therapeutic footwear that has a demonstrated plantar pressure‐relieving effect during walking (i.e. 30% relief compared with plantar pressure in standard of care therapeutic footwear) and encourage the patient to wear this footwear. (Strong; Moderate) To prevent a first foot ulcer in an at‐risk patient with diabetes, provide education aimed at improving foot care knowledge and behaviour, as well as encouraging the patient to adhere to this foot care advice. (Weak; Low) To prevent a recurrent foot ulcer in an at‐risk patient with diabetes, provide integrated foot care, which includes professional foot treatment, adequate footwear and education. This should be repeated or re‐evaluated once every 1 to 3 months as necessary. (Strong; Low) Instruct a high‐risk patient with diabetes to monitor foot skin temperature at home to prevent a first or recurrent plantar foot ulcer. This aims at identifying the early signs of inflammation, followed by action taken by the patient and care provider to resolve the cause of inflammation. (Weak; Moderate) Consider digital flexor tenotomy to prevent a toe ulcer when conservative treatment fails in a high‐risk patient with diabetes, hammertoes and either a pre‐ulcerative sign or an ulcer on the distal toe. (Weak; Low) Consider Achilles tendon lengthening, joint arthroplasty, single or pan metatarsal head resection, or osteotomy to prevent a recurrent foot ulcer when conservative treatment fails in a high‐risk patient with diabetes and a plantar forefoot ulcer. (Weak; Low) Do not use a nerve decompression procedure in an effort to prevent a foot ulcer in an at‐risk patient with diabetes, in preference to accepted standards of good quality care. (Weak; Low)